A Gram-Scale Synthesis of Enantiomerically Pure (R)- and (S)-δ-Heptalactone, Pheromones of Fruit Flies - Kiuchi, Tatsuya; Stamm, Patrick; Schulz, Stefan (Synthesis, 2025)
Stereochemistry plays a crucial role in pheromone communication among many insects, and pure enantiomers of pheromones are often required to unambiguously evaluate their biological activity. The buckthorn fly, Rhagoletis batava, is attracted to its pheromone (S)-(−)-heptalactone (5-heptanolide), but is potentially deterred, possibly also in a sex-dependent manner, by the (R)-enantiomer. Therefore, larger amounts of highly pure enantiomers of this lactone were needed to clarify their function and attractiveness in the field. We describe here a simple synthesis that enables the preparation of both enantiomers with an enantiomeric excess (ee) greater than 99.5% on a gram scale, investigating several routes. The best and most reliable results were obtained by starting with the racemate resolution of ethyloxirane using Jacobsen’s Co-salen complex, followed by Grignard addition of a 3-butenyl group, ozonolysis, and immediate PCC oxidation. Other procedures, such as enzymatic resolution, were less reliable in our hands and did not achieve such high ee values for both enantiomers.
Keywords: Semiochemicals; g-Scale synthesis; Insects; Jacobsen epoxide resolution; Enantioselective synthesis; Ozonolysis